ANALISIS KETERTARIKAN GENERASI MILENIAL UNTUK PERANCANGAN BATIK MALANGAN - Syafira Audianty; Yan Yan Sunarya (Universitas Ciputra Surabaya, 2021)
Motif is a creativity that is formed from the inspiration of the people who living in it, so it different from one place to another. Malangan lotus flower batik motifs is one of the examples, but this icon and batik motif is still less desirable so there are efforts to popularize Malangan batik. This design development is not only aims to produce new batik designs that are in accordance with local wisdom, but also has a social and economic impact. With ATUMICS method, it become an investment for the Malang area in the future. The revitalization is aimed to creating new batik designs for the millennials who are considered to have the power to boost the regional economy and wealth. This research aims to analyze and understand the millennial’s interest in traditional batik and the development of Malang lotus flower batik to create new batik designs. The analysis includes the millennial generation's interest in visuals and batik fashion products. The research method used is a mixed method, a qualitative method is to obtain literature studies, on the other hand quantitative method is to get the millennial respondents. From this research, it can be concluded that the visual and design product are important variables in the development of new design batik Malangan lotus flower, so that it can be a reference in increasing commercial value and attractiveness to the community. Keywords: Batik, Local Wisdom, Lotus, Malang, Millennial Generation.